2014
DOI: 10.1016/j.oceaneng.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Long term immersion in natural seawater of Flax/PLA biocomposite

Abstract: International audienceInnovation in sailing yacht design must include current environmental concerns such as resource depletion and waste management. Indeed most of the materials used today are petro-based and cannot offer viable end of life treatment. Fully biodegradable natural fibre reinforced biopolymers are being increasingly studied as they offer high specific stiffness and low environmental footprint. However, their ageing mechanisms are still not well understood.The present article gives information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 43 publications
4
52
0
2
Order By: Relevance
“…It was suggested that because of increased amount of absorbed water in the composites, this resulted to swelling of the fibres and filled the openings between the hemp fibre-polymer interfaces and eventually led to an increase in the mechanical properties of the composites. Improved Young's modulus was observed in the investigation of flax/PLA biocomposites immersed in seawater (Le Duigou, Bourmaud, Davies, & Baley, 2014). The composite rigidity was evaluated between 0.025 and 0.1% range, and the Young's modulus of the composites immersed in seawater was found to increase until 0.5% range to 32 MPa.…”
Section: Natural Fibres and Compositesmentioning
confidence: 99%
“…It was suggested that because of increased amount of absorbed water in the composites, this resulted to swelling of the fibres and filled the openings between the hemp fibre-polymer interfaces and eventually led to an increase in the mechanical properties of the composites. Improved Young's modulus was observed in the investigation of flax/PLA biocomposites immersed in seawater (Le Duigou, Bourmaud, Davies, & Baley, 2014). The composite rigidity was evaluated between 0.025 and 0.1% range, and the Young's modulus of the composites immersed in seawater was found to increase until 0.5% range to 32 MPa.…”
Section: Natural Fibres and Compositesmentioning
confidence: 99%
“…Moreover, when composites are exposed to a humid environment, the value of loss factor peaks increases with the exposition time to humid environments and, consequently, moisture content [40]. This detrimental effect is more pronounced for composites characterized by a weak fiber-matrix interface because they dramatically suffer mechanical performance degradation when exposed to humid environments during their service life [12,13].…”
Section: Laminate 30 Days 60 Daysmentioning
confidence: 99%
“…Natural fiber-reinforced composites (NFRPs) have received growing attention in the last decades, both from the academic world and from industries, thanks to their specific mechanical properties, reduced cost and advantages for health and recyclability. Nevertheless, this class of innovative materials shows also some drawbacks, such as their limited aging resistance in humid or wet environmental conditions, i.e., an extensive literature shows that NFRP materials experienced dramatic degradation of their quasi-static mechanical properties when exposed to these environments [10][11][12][13][14][15][16][17][18]. This can be partially ascribed to the softening and plasticization phenomena of natural fibers and thermoset matrix [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, the properties of natural fibres changes significantly during their use in a moisture environment [9][10][11][12][13]. Indeed, several works have proved that the mechanical properties of natural fibres are significantly affected when they are exposed to humidity [9][10][11][12][13]. Thereby, it now becomes interesting or important to reduce these effects which are a crucial problem for the development of natural fibre reinforced polymer composite materials.…”
Section: Introductionmentioning
confidence: 99%